To solve the equation \(2x - 5 = 3(4x + 5)\), we can follow these steps:
Step-by-step Breakdown:
Step 1: Apply the Distributive Property to get 2x - 5 = 12x + 15.
- (Part 1: D, Part 2: A)
Step 2: Apply the Addition of Equality property to get 2x - 12x = 15 + 5.
- (Part 1: A, Part 2: B)
Step 3: Apply the Combine Like Terms property to get -10x = 20.
- (Part 3: B, Part 3: A)
Step 4: Apply the Division of Equality property to get x = -2.
- (Part 4: D, Part 4: C)
Here’s the full fill-in of the blanks based on the sequential reasoning:
Final Answer:
Step 1: D. Distributive Property to get A. \(2x - 5 = 12x + 15\)
Step 2: A. Addition of Equality Property to get B. \(2x - 12x = 15 + 5\)
Step 3: B. Combine Like Terms Property to get A. \(-10x = 20\)
Step 4: D. Division of Equality Property to get C. \(x = -2\)